2020
DOI: 10.1101/2020.09.15.20195255
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, attitudes and practices associated with the COVID-19 among slum dwellers resided in Dhaka City: A Bangladeshi interview-based survey

Abstract: Background: The emergent COVID-19 has impacted unprecedentedly to all classes of people. Slum-dwellers' knowledge, attitudes and practices (KAP) towards COVID-19 are currently poorly understood. To investigate the KAP towards COVID-19 among slum dwellers resided in Dhaka City, Bangladesh. Methods: A cross-sectional offline survey was carried out enrolling 406 slum dwellers (53.2% male; mean age=44.9 years [SD=12.1]; age range=18-85 years) between August and September, 2020. The face to face interview was condu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
2
13
1
Order By: Relevance
“…This finding is similar with other studies in Bangladesh demonstrating no significant sex differences in knowledge regarding COVID-19 [ 26 , 27 ]. This finding is similar to studies concerning knowledge towards COVID-19 (not vaccinations) conducted in Bangladesh which reported that males had marginally higher scores in knowledge regarding COVID-19 than females [ 28 , 29 ]. However, this finding is inconsistent to studies concerning knowledge towards COVID-19 (not vaccinations) conducted in Bangladesh which reported that males had marginally higher scores in knowledge regarding COVID-19 than females [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This finding is similar with other studies in Bangladesh demonstrating no significant sex differences in knowledge regarding COVID-19 [ 26 , 27 ]. This finding is similar to studies concerning knowledge towards COVID-19 (not vaccinations) conducted in Bangladesh which reported that males had marginally higher scores in knowledge regarding COVID-19 than females [ 28 , 29 ]. However, this finding is inconsistent to studies concerning knowledge towards COVID-19 (not vaccinations) conducted in Bangladesh which reported that males had marginally higher scores in knowledge regarding COVID-19 than females [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 87%
“…This finding is similar to studies concerning knowledge towards COVID-19 (not vaccinations) conducted in Bangladesh which reported that males had marginally higher scores in knowledge regarding COVID-19 than females [ 28 , 29 ]. However, this finding is inconsistent to studies concerning knowledge towards COVID-19 (not vaccinations) conducted in Bangladesh which reported that males had marginally higher scores in knowledge regarding COVID-19 than females [ 28 , 29 ]. These discrepancies of knowledge found in our study on COVID-19 vaccinations are possibly due to limited government exposures to information or publicity on COVID-19 vaccinations since the vaccine rollout started.…”
Section: Discussionsupporting
confidence: 87%
“…Since then, the virus has spread worldwide, with millions of COVID-19 cases and related deaths being recorded globally [4]. The first case of COVID-19 was confirmed in Bangladesh on March 8, 2020 [5,6,7], and more than 317,500 confirmed cases of COVID-19 and 4,351 deaths have been recorded by September 03, 2020 [8].…”
Section: Introductionmentioning
confidence: 99%
“…A study in Bangladesh also found that sociodemographic factors such as high family income correlated with a more positive attitude towards COVID-19 [25]. Multiple studies conducted in various countries have shown similar results [26], [27], [28], [29].…”
Section: Discussionmentioning
confidence: 79%